Investigations of dnepropetrovsk mathematicians related to inequalities for derivatives of periodic functions and their applications - Babenko, V. F. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We present a survey of investigations of Dnepropetrovsk mathematicians related to Kolmogorov-type exact inequalities for norms of intermediate derivatives of periodic functions and their applications in approximation theory.